Sustainable Supply Chain Management Practices and Sustainability Performance in the Food Industry - Emamisaleh, Korosh; Rahmani, Kamaleddin; Iranzadeh, Soleyman (UI Scholars Hub, 2018)
Sustainable development has recently been identified as a challenge for many countries and has become a vital issue for food-related industries. This study of sustainable supply chain management practices and sustainability performance in the food industry was conducted at food companies in Iran. Data were gathered from 120 companies by means of a questionnaire; confirmatory factor analysis (CFA) was used to test the questionnaire’s validity. Hypotheses were tested by path analysis. The results of Structural Equation Modeling (SEM) indicate that sustainable supply chain management practices impact on the environmental, economic, and social dimensions of sustainability. Based on these findings, there is a need to improve sustainable supplier management practices, sustainable operations management practices and sustainable customer management practices in order to advance sustainability performance in the supply chain.